Social Media Strategies in the Early Stage of the Corona Pandemic in the Kingdom of Bahrain: An Analytical Study - Al-Saqer, Layla Hasan (Journal of Humanities & Social Sciences, 2022)
This paper discusses the increasing importance of strategic social media for government institutions during the Corona pandemic and the communication strategies used in the Instagram account of the Ministry of Health in the Kingdom of Bahrain in the early stage of the pandemic. The study combines both quantitative and qualitative methodological approaches, where the researcher used quantitative content analysis of the early stage of the launch of the national campaign to combat the Coronavirus in the Kingdom of Bahrain by analysing social media strategies used in the Instagram account based on the Reynolds & Seeger (2005) model of crisis communication strategies. In addition, the researcher used the qualitative analysis of digital content based on the theoretical framework based on social semiotics provided by Kress and Leeuween (1996) to analyse the extent to which digital content of the social media campaign has “enabled” the target audience to be a partner in social change. The study finds that the Ministry of Health used communication strategies proactively in the early stage of the Corona pandemic. The community partnership strategy came first with a percentage of 33.33% and the media strategy with a percentage of 32.34%. The study confirmed the interaction of the Bahraini society with the publications of the Ministry of Health on the Instagram account, because of the interactive nature of social media. The symbolic interaction with “likes” reached (100%), while the number of interactions with comments on the posts reached 65.35%. The study calls for strengthening the role of social media strategies in "empowering" and involving the target audience in positive change in society. The study comes out with a set of recommendations that urge adopting innovative social media strategies to empower societies to overcome the crisis.
Keywords: Strategies; social media; Corona pandemic; Social empowerment; Crisis Management